Revitalisasi Fungsi SDM Polri dan Anggaran Polri Menuju Kemandirian dan Profesionalisme Polri - M. Gausyyah (Universitas Syiah Kuala, 2012)
ABSTRACT: This article aims to provide explanation in regards to conduct the police human resource reform and police budget as part of police reform. Human Resource planning system, selection and recruitment process system, career path, reward and punishment system, and remuneration system will support the achievement of Police professionalism. Police budget revitalization by conducting the budget oriented program is the strategic effort to achieve the police independence. The Revitalisation of Human Resource Function and Indonesian National Police Budget Heading to Its Independency and Profesionalism